Constructive Strategies of Speaking Skill Using Smart Thinking, Searching Online, Practicing Solution (3S) Implementation Model to be Spoken Fluently At SMA NW Anjani, East Lombok - Lukman Jayadi (Innovative Pedagogy and Education Studies, 2026)
This research aims to develop effective strategies for enhancing speaking skills through the applying 3S (Smart Thinking, Online Searching, and Solution Practice) model, with the goal of improving students' English-speaking fluency. The primary challenge on speaking learning process is students' limited ability to convey ideas systematically, confidently, and effectively due to a lack of mastery of basic vocabulary and material. Therefore, the 3S model presents an innovative approach that integrates critical thinking skills, the use of digital technology, and direct practice in real-life communication situations. This research method uses a descriptive qualitative approach and quantitative with the application of a practice-based, active, and more communicative learning model. The stages of implementing the 3S model include: (1) Smart Thinking, or intelligent thinking to construct ideas and arguments logically and rationally, and easily understood by listeners or conversation partners; (2) Online Searching, which involves seeking references and information through digital media to enrich speaking material and expand basic vocabulary; and (3) Solution Practice, which involves active speaking practice through discussions, presentations, and more active communication simulations while their imagine words that will be spoken. Data were obtained through observation, interviews, recordings, and evaluation of students' speaking skills. The research results show that the implementation of the 3S model can improve students' English fluency, ability to organize ideas effectively, communication skills, creativity in expressing opinions, and explore their knowledge through 3S by spoken fluently.  Furthermore, the use of digital media is quite proficient and has a positive impact on students' learning motivation and ability to access information independently. Therefore, a constructive strategy based on the 3S model is considered effective as an alternative method for teaching speaking skills that is adaptive, interactive, creative, and relevant to current developments in modern educational technology.